Inclusive Family Led Field Days in Baringo County, Kenya - Majiwa, Hamilton; Bullock, Renee (International Livestock Research Institute, 2025)
AICCRA Kenya cluster’s focus is in arid and semi-arid lands (ASALs), that make up nearly 90% of Kenya’s land cover. Approximately 38% of Kenya’s population reside in ASALs and climate change effects in drylands include severe and prolonged drought and flooding (Bullock, 2022). Climate smart agriculture and climate information systems have the potential to reduce risk and build resilience for better livelihoods in drylands. Gender is a crosscutting theme across Kenya Cluster that is composed of five thematic areas. The overall objective of the cluster is to scale socially inclusive climate smart agricultural (CSA) technologies and climate information services (CIS) in drylands with a focus on women and youth. An intersectional approach is used to understand power relations and social factors that shape scaling of CSA and CIS practices, including gender, age, ethnicity, and wealth among others. Efforts to scale CSA and CIS into Baringo County began in 2024 and included an exchange visit to Kitui and Makueni counties (Bullock, et. al., 2024), whereby Baringo pastoralists and agropastoralists, agricultural extension officers and the sub-county agricultural officer (SCAO) travelled for a peer learning exchange. ILRI and Baringo county agricultural extension officers supported demonstration farms that function as socially inclusive learning hubs where women, men and youth can learn about the CSA technologies and practices. ICRISAT provided 250 famers with starter seed packs of legumes and cereals in 2024. Over half of the recipients were women. Field planning efforts were made to then host and support a field day premised on socially inclusive and locally led adaptation principles in Paka location, Loyamorok ward on 17th May 2025.